Sulla (ri)articolazione della “marocchinità” nel Marocco contemporaneo, tra festivalizzazione del dissenso giovanile e revival sufi - Michela Buonvino (Archivio Antropologico Mediterraneo)
This article aims to provide the reader with a general overview of the dynamics that characterize cultural festivalization in contemporary Morocco, examining the processes of rearticulation of rhetoric and policies related to national identity and culture implemented by the Moroccan state since Independence (1956). These processes are aimed at the (re)production and redistribution of a state cultural hegemony in a transnational context. Specifically discussed here, reconstructing their key moments, and highlighting some points of contact, are two distinct and interconnected depoliticizing strategies: the festivalization of youth discontent and the strategic revitalization of Sufism, pursued respectively since the mid-1990s and the early 2000s. These processes are part of a broader design of social discipline aimed at maintaining political order and the state's monopoly on religious identity. After September 11, 2001, and following terrorist attacks in Casablanca, the Moroccan monarchy was engaged in redefining a field of the sacred, which involved the neutralization of Salafist tendencies and their replacement with a Sufism deemed harmless and incapable of threatening the nation's spiritual security. The monarchy's discursive strategies required and still require the elaboration of public representations of virtue, particularly of the principle of democratic citizenship, central in the transitional discourses of today's Moroccan state, performed within the framework of national and international festivals. This type of communication serves to strengthen and promote specific "civilizing processes" that include particular "disciplines of belonging" to the nation and the community of believers.